MODELING OF A DNA IDENTIFICATION SYSTEM BASED ON THE IDEF0 MODEL (Uzbekistan Open Conference, 2026)
This article examines the problem of modeling a DNA (deoxyribonucleic acid) identification system based on the IDEF0 model. The complexity of DNA examination processes requires their functional systematization. For this purpose, the input, output, control, and mechanism elements of the system are defined using the IDEF0 methodology. The stages of DNA sample processing, comparison with databases, and generation of identification results are modeled. The proposed model aims to optimize the identification process and ensure the accuracy of decision-making.